Quantitative analysis of myocardial fibrosis in normals, hypertensive hearts, and hypertrophic cardiomyopathy. Issue 6 (June 1986) - Tanaka, M; Fujiwara, H; Onodera, T; Wu, D J; Hamashima, Y; Kawai, C
Abstract : The distribution of fibrosis was studied quantitatively in the entire left ventricular wall of a transverse slice of the heart from 10 necropsy cases of hypertrophic cardiomyopathy, 10 cases of hypertensive heart disease, and 20 normal adults. The percentage area (mean (SD)) of fibrosis in the left ventricular wall in hypertrophic cardiomyopathy (10.5 (4.3)%) was significantly greater than that in hypertensive heart disease (2.6 (1.5)%) or in normal hearts (1.1 (0.5)%). In hypertrophic cardiomyopathy the percentage area of fibrosis was greater (13.1 (4.8)%) in the ventricular septum than in the left ventricular free wall (7.7 (4.2)%) whereas in hypertensive heart disease and normal hearts values in these two areas were similar. The percentage area of fibrosis in the left ventricular free wall (where myocardial fibre disarray was not extensive even in hypertrophic cardiomyopathy) was greater in hypertrophic cardiomyopathy than in hypertensive heart disease. The percentage area of fibrosis correlated with heart weight in hypertensive heart disease, but not in hypertrophic cardiomyopathy. These results suggest that widespread fibrosis in hypertrophic cardiomyopathy cannot be explained by cardiac hypertrophy alone, and that disarray and other factors are also important in pathogenesis. The increase in the percentage area of fibrosis from the outer to the inner third of the left ventricular free wall in hypertrophic cardiomyopathy and in hypertension probably reflected transmural gradients of wall stress and myocardial fibre diameter. Although fibrosis is not specific to hypertrophic cardiomyopathy, its quantification and analysis of its regional distribution provide information that is useful in investigating the pathophysiology of the disorder.